Influence of a material and the technological factors on improvement of operating properties of machine parts by reliefs and film coatings - Posviatenko, Eduard; Posviatenko, Nataliia; Budyak, Ruslan; Shvets, Ludmila; Paladiichuk, Yurii; Aksom, Petro; Rybak, Ilya; Sabadash, Bogdan; Hryhoryshen, Valentyn (Eastern-European Journal of Enterprise Technologies, 2018)
A joint effect of preliminary cold plastic deformation and environmentally friendly lubricating substances of plant origin on the improvement of machinability of austenitic steels was considered. This extends the use of such steels as structural material in machine building. The influence of micro- and macroreliefs of machined parts both as technological and operational factors was explored. The former involves division of allowances during machining deep openings, and the latter involves the improvement of operational characteristics of the surface of a part. The influence of film coatings on an increase in durability of rolling bearings was studied. In particular, it was found that these coatings heal micro cracks from grinding of rolling bearings cases and bodies and increase the reliability of these crucial parts by increasing the level of hardness. It was shown that the curvature of the generatrix of deep openings should be decreased by changing the directions of major movements in the related operations. It was established that special attention should be paid to the heredity of machining. The ways of improvement of machinability of austenitic steels were substantiated. This is the use of preliminary cold plastic deformation to execute a part of work of cutting and transferring paramagnetic status of steels into magnetic. It is also the use of environmentally friendly lubricants of plant origin during cutting. The dual purpose of the reliefs of the surface of a part – technological and operational – was established. The former is executed by a special broaching tool and is effective during machining deep openings. The purpose of the latter is to create labyrinths for lubricants and division of shells into separate elements. The mechanism of the action of vacuum film coating on reliability of rolling bearings, which contributes to healing micro cracks from the preliminary abrasive treatment and an increase in surface hardness, was studied. It was shown that a decrease in the height of curvilinearity and waviness of deep openings is achieved by the change in the main motion of the related operations. Results of the research are the basis for creating technologies of critical machine parts in production